Перспективы формирования системы коллективной безопасности в Азии: сравнительный анализ с европейской системой безопасности. Возможности для казахстанской дипломатии (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
At the current stage of transformation of international relations, within the framework of Asian geopolitics, there is a need to create collective security institutions. The main current model is the European system of collective security, the experience of which is important for Asia. The security system in Asia is characterized by the fact that it is still dominated by elements of the classical Westphalian model of international relations, namely nation-states. For the formation of a collective security system, several certain factors play an important role, among which we can mention the military-technical component, polarity, as well as the socialization factor. This article, within the framework of the study, points out that the key role is played by these three factors. The formation of such a security system is also important for diplomacy in Kazakhstan, which is the initiator and promoter of CICA, an international forum for strengthening cooperation aimed at ensuring peace, security, and stability in Asia.Although in the short term, the formation of a collective security system in Asia seems unlikely, there are all the prerequisites and potential in the medium or long term.